Policy perspectives on post pandemic influenza vaccination in Ghana and Malawi - Evanson Z. Sambala; Lenore Manderson (BMC, 2017)
Abstract Background In the late 1990s, in the context of renewed concerns of an influenza pandemic, countries such as Ghana and Malawi established plans for the deployment of vaccines and vaccination strategies. A new pandemic was declared in mid-June 2009, and by April 2011, Ghana and Malawi vaccinated 10% of the population. We examine the public health policy perspectives on vaccination as a means to prevent the spread of infection under post pandemic conditions. Methods In-depth interviews were conducted with 46 policymakers (Ghana, n = 24; Malawi, n = 22), identified through snowballing sampling. Interviews were supplemented by field notes and the analysis of policy documents. Results The use of vaccination to interrupt the pandemic influenza was affected by delays in the procurement, delivery and administration of vaccines, suboptimal vaccination coverage, refusals to be vaccinated, and the politics behind vaccination strategies. More generally, rolling-out of vaccination after the transmission of the influenza virus had abated was influenced by policymakers' own financial incentives, and government and foreign policy conditionality on vaccination. This led to confusion about targeting and coverage, with many policymakers justifying that the vaccination of 10% of the population would establish herd immunity and so reduce future risk. Ghana succeeded in vaccinating 2.3 million of the select groups (100% coverage), while Malawi, despite recourse to force, succeeded only in vaccinating 1.15 million (74% coverage of select groups). For most policymakers, vaccination coverage was perceived as successful, despite that vaccination delays and coverage would not have prevented infection when influenza was at its peak. Conclusions While the vaccination strategy was problematic and implemented too late to reduce the effects of the 2009 epidemic, policy makers supported the overall goal of pandemic influenza vaccination to interrupt infection. In this context, there was strong support for governments engaging in contracts with pharmaceutical companies to ensure the timely supply of vaccines, and developing well-defined guidelines to address vaccination delays, refusals and coverage.